The ZZ Domain of Dystrophin in DMD: Making Sense of Missense Mutations. Issue 2 (2nd December 2013) - Vulin, Adeline; Wein, Nicolas; Strandjord, Dana M.; Johnson, Eric K.; Findlay, Andrew R.; Maiti, Baijayanta; Howard, Michael T.; Kaminoh, Yuuki J.; Taylor, Laura E.; Simmons, Tabatha R.; Ray, Will C.; Montanaro, Federica; et al.
<x xml:space="preserve">Abstract</x> Missense mutations in the dystrophin ZZ domain result in Duchenne muscular dystrophy. In vivo studies of two mutations of zinc‐finger defining cysteine residues (p.Cys3313Tyr and p.Cys3340Tyr) and one non‐cysteine mutation (p.Asp3335His) demonstrate no β‐dystroglycan binding of any, but this is due to two different mechanisms. The cysteine mutations result in unstable proteins that are rapidly degraded, whereas the aspartic acid mutation interferes with β‐dystroglycan binding despite normal localization to the sarcolemmal membrane, possibly mediated by preserved a‐syntrophin binding (co‐immunoprecipitation, right). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>